Le Corbusier: ambiguous structure and grid dissolution - Zaparaín Hernández, Fernando; Ramos Jular, Jorge; Llamazares Blanco, Pablo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
This article proposes a comparative analysis of Le Corbusier’s use of the most characteristic structural system of modernity: the “plan libre” grid. He defined it in the prototype Dom-ino, and the "five points". First the Oeuvre Complète, and then, the scholars, they settled the formal value of an ordering and independent grid. But a careful analysis of the documents, and their contrast with the structure schemes of the buildings, reveals an ambiguity, richer and more complex. The apparent homogeneous and exempt grid suffers deliberate alterations: unidirectional frames, suppression of pilotis in certain nodes, displacement of others outside the axes, concealment between the walls, deformation of sections, manifestation of pipelines and chimneys as if they were pilotis or apparition of hanging beams, disturbing the supposed flatness of the ceiling. Despite these peculiarities, the results show that sufficient references are conserved as to maintain legible the grid, while the anomalies propitiate juicy plastic contrasts between ideal solids. This ambiguity is put at the service of a greater formal "poetry", while maintaining the "rationalism" of a base grid that structures the floor and guides the project process. In addition, while Le Corbusier was advancing in "the 4 compositions", he was increasing the dissolution of the structure, also in the upper floors.